The Influence of Competence, Motivation, and Compensation on the Work Spirit of Employees at Sungai Penuh Community Health Center, Sungai Penuh District - Efrianto, Efrianto (The Future of Education Journal, 2025)
This study aims to analyze the influence of competence, motivation, and compensation on the work spirit of employees at the Sungai Penuh Community Health Center (Puskesmas), Sungai Penuh District. The main issue addressed in this research is the low work morale of employees despite the fact that these factors have been relatively well-managed. The method used is a quantitative approach, with data collected through questionnaires and documentation. The sample consists of employees at the Sungai Penuh Health Center, selected using a simple random sampling technique. The results indicate that competence, motivation, and compensation have a weak relationship with work spirit, with significance values greater than 0.05. Multiple linear regression analysis shows that these three variables together explain only 21.7% of the variation in employee work spirit. These findings suggest that other factors not identified in this study may have a greater influence on employee morale at the Sungai Penuh Health Center.